THE EFFICACY AND SAFETY OF A POLYPILL (ANTIHYPERTENSIVE, STATIN, ± ASPIRIN) FOR THE PRIMARY PREVENTION OF MAJOR ADVERSE CARDIOVASCULAR EVENTS: A SYSTEMATIC REVIEW AND META-ANALYSIS - Warham; Jonea Octavien Wijaya; Widya Aulia; Sammy Samuel; Bram Adhitama (PT. Jurnal Center Indonesia Publisher, 2025)
Background: Cardiovascular disease (CVD) continues to be the predominant cause of global mortality. Polypill techniques that integrate various cardiovascular drugs into a single formulation have emerged as a potential method for primary prevention, especially in intermediate-risk populations. Objective: To systematically review and synthesize evidence regarding the efficacy and safety of polypill formulations (comprising antihypertensive medications, statins, with or without aspirin) in comparison to standard care or placebo for the primary prevention of major adverse cardiovascular events (MACE) in intermediate-risk populations. Methods: We conducted systematic review and meta-analysis in accordance with PRISMA 2020 standards (Systematic Review Registration: PROSPERO CRD420251184718). Various databases (PubMed, Cochrane Library, ScienceDirect, Scopus) were examined for original research published from January 2015 to October 2024. Studies were eligible if they assessed polypill therapies in individuals aged 30 to 70 years with intermediate cardiovascular risk (10-20% 10-year risk), reported composite major adverse cardiovascular events (MACE) outcomes, and included a minimum follow-up of 6 months. Two independent reviewers conducted screening, data extraction, and risk of bias evaluation utilizing the Cochrane RoB 2.0 tool. Results: Of the 161 records discovered, 4 randomized controlled studies (HOPE-3, TIPS-3, PolyIran, PolyPars) with 31,501 people fulfilled the inclusion criteria. Polypill therapies showed a substantial decrease in composite MACE relative to control groups (pooled HR 0.67 (95% CI 0.60-0.75, p<0.001). Individual trial hazard ratios varied from 0.50 (PolyPars) to 0.66 (PolyIran) and 0.79 (TIPS-3) with moderate heterogeneity (I²=35.2%, p=0.20). Polypills were generally well- tolerated, with a safety profile consistent with the individual components. Medication adherence was enhanced with the polypill in comparison to multiple-pill regimens. Conclusions: Polypill techniques markedly reduce major adverse cardiovascular events (MACE) in intermediate-risk patients for primary cardiovascular prevention, achieving around a 33% relative risk reduction. The fixed-dose combination strategy provides benefits in compliance and ease of use. These findings hold significant implications for healthcare systems in low-to- middle-income nations, such as Indonesia, where the burden of cardiovascular disease is substantial and access to long-term cardiovascular drugs is frequently hindered by cost and complexity.